Targeted Intervention for Long-Term English Learners’ English Language Development and Reading Outcomes - Angela Johnson; Diana Mercado-Garcia (AERA Open)
This study examines College Access (pseudonym), a program which aims to improve English proficiency, access to academic content, and college readiness for middle school students labeled as Long-Term English Learners. Program participants tended to score higher in English proficiency than students in Newcomer English language development (ELD), other ELD, or not receiving designated ELD services. College Access is also associated with higher English Language Arts (ELA) and reading scores relative to students in Newcomer ELD, similar ELA scores and higher reading scores relative to students in other ELD, and lower scores relative to no designated ELD service. These results hold with and without controls for prior-year test scores. Within-year reading growth rates for College Access were lower or similar compared to the other groups.